PERAN FESTIVAL HIBURAN DALAM MENDORONG PARIWISATA PERKOTAAN DI SURABAYA - Ariana Zakinah; Garsione Agni Andrea (Halu Oleo University, 2025)
This study aims to analyse the role of entertainment festivals, particularly music festivals, in shaping the image and attractiveness of urban tourism in Surabaya. The city is undergoing a transformation as a hub for urban tourism and MICE (Meeting, Incentive, Convention, and Exhibition), leveraging its cultural assets and local creativity as key elements in city branding strategies. This study adopts a qualitative approach using library research to examine relevant academic journals, policy reports, scholarly books, and case studies published within the last five years. The findings indicate that entertainment festivals function not only as recreational platforms but also as symbolic media that convey the city’s identity in visual and emotional forms to visitors. Surabaya has successfully incorporated events such as Jazz Traffic Festival, Surabaya Vaganza, and Sound of Downtown into a creative and inclusive urban narrative. The analysis is grounded in the Destination Marketing Triangle framework and the semiotics of festivals, illustrating how collaboration between local stakeholders, event organisers, and tourists creates a cohesive perception of the destination. This study concludes that entertainment festivals serve as vital catalysts for constructing authentic city imagery, fostering tourist loyalty, and supporting the sustainable development of urban tourism.